The nuclear envelope and nuclear pore complexes in neurodegenerative diseases - Wu, Tingyan; Xu, Haochen; Cheng, Lei; Wu, Ruoxin; Guo, Fuzheng; Chen, Xi (Frontiers in Cell and Developmental Biology, 2025)
The nuclear envelope (NE) and nuclear pore complexes (NPCs) play a critical role in maintaining the balance between the nucleus and cytoplasm, which is essential for the structural integrity and gene regulatory functions of eukaryotic cells. Disruptions in the nucleocytoplasmic trafficking mediated by the NE and NPCs can compromise nuclear integrity and transport homeostasis, ultimately threatening cellular viability. Recent research has highlighted a strong link between dysfunction of the NE and NPCs and the onset of neurodegenerative disorders. In this review, we summarize the current understanding of how impairments in nuclear transport contribute to the pathogenesis of neurodegenerative diseases, with a particular focus on the NE and NPCs. We aim to shed light on the intricate relationship between these molecular gatekeepers and the pathological cascade leading to neuronal degeneration, while also exploring potential strategies to restore cellular homeostasis and mitigate the progression of these devastating neurological conditions.